Ketogenic Diet-induced Severe Ketoacidosis in a Lactating Woman: A Case Report and Review of the Literature (FS17-01-19). (13th June 2019) - Nnodum, Benedicta; Oduah, Eziafa; Albert, David; Pettus, Mark
Abstract: Objectives: Ketogenic diet is a high-fat, adequate-protein, and low-carbohydrate diet that leads to nutritional ketosis and weight loss. Although ketogenic diet is safe in non-pregnant individuals, its safety in lactating mothers is unknown. Methods: 24-year-old 18 weeks' post-partum healthy non-diabetic woman complained of severe nausea, vomiting and diarrhea with associated abdominal pain, low back cramps & malaise. She reported intentional 25-pound weight loss by adhering to strict ketogenic diet as a health-conscious life style modification since recent childbirth. She exclusively breastfed her son. She had unremarkable pre, natal and postnatal care. Typical diet consisted of egg, bacon, cheese, meat, peppers, spinach, broccoli, carrot soups, chicken, salmon, peanut butter. Daily caloric intake was approximately 2200 Kcals/day. She was hemodynamically stable. Physical examination revealed dry mucous membranes, comfortable resting tachypnea, mild epigastric/right upper quadrant tenderness. Laboratory studies demonstrated compensated anion gap metabolic acidosis acidaemia, elevated beta-hydroxybutyric acid level (Figure 1) and ketonuria. She was managed conservatively with intravenous fluids, electrolyte repletion, and restarting carbohydrate diet. Results: Lactation ketoacidosis is well described in post-partum lactating cattle. Few case reports in human exist. Most cases were precipitated by starvation, infection or nil per mouth status (table 1 ). It occurs by depletion of glycogen stores forcing the body into using gluconeogenesis as energy substrate for breast milk production. This is the first case report of life-threatening lactation ketoacidosis in setting of ketogenic diet with adequate number of calories, above 2000 kcal/day. Ketogenic diet is an alternative weight loss tool against obesity due to proven results of greater weight loss compared to other balanced diets. Studies that evaluated acid-base safety of patients on ketogenic diet demonstrated no significant metabolic derangement. Patients who ate plant-derived protein have lower mortality compared to those who ate animal-derived protein and fat. Postpartum mothers have increased pressure to lose weight gained during pregnancy and may easily resort to this method of rapid weight loss. Conclusions: The index case may provide caution in lactating mothers on/or considering ketogenic diet. Healthcare professionals need to educate lactating mothers interested in weight loss. Funding Sources: There are no funding sources. Supporting Tables, Images and/or Graphs: